Sistem Pendukung Keputusan Menentukan Kelayakan Calon Pengantin Dengan Metode SAW di Kabupaten Pasangkayu - Ardiansyah; Adam M Tanniewa (Prosiding SISFOTEK, 2023)
The rate of early marriage in Pasangkayu Regency has increased to 14.68%, making it occupy first position in West Sulawesi. This resulted in the DP3AP2KB of Pasangkayu Regency working hard in granting marriage permits, even though the selection process carried out by the DP3AP2KB of Pasangkayu Regency was still manual and not properly computerized. To overcome this, it is necessary to build a system to streamline the selection process for prospective brides and grooms who are well computerized. This system will utilize the Decision Support System (SPK) process using the Simple Additive Weighting (SAW) method which focuses on six criteria, namely age, employment, education, parental permission letter, SKBS, and tetanus injection. The output produced is in the form of a ranking table which will make it easier to determine the suitability of prospective brides and grooms. The results of this research show that 3 prospective brides (6%) were declared "Very Eligible" for marriage with a reference value between 0.850 to 1.000; Furthermore, 29 prospective brides (58%) were declared "Suitable" for marriage with a reference value between 0.650 to 0.849 and 18 prospective brides (36%) were declared "Considering" for marriage with a reference value between 0.000 to 0.649.